A study on emotional maturity and gender differences in government employees - Rajkumar, A. (University of Jaffna, 2012)
The emotional maturity becomes important in the behavior of people. It is one of the main determining aspects for the success of people. The present study investigates the emotional maturity and gender differences in government employees. A random sample consisted of 100 government employees was drawn from the Municipal Council, Jaffna. Standardized scale namely emotional maturity scale was administered to assess the emotional skills like emotional stability, emotional regression, social maladjustment, personality disintegration and lack of independence. The collected data were tabulated, processed and analysed by employing statistical techniques like standard deviation and t-test. The results of the study indicated that the female employees were found significantly better than the male employees in the area of emotional maturity skills and there is a significant gender difference in emotional maturity. It was also noticed that employees in the government sector are emotionally unstable.